A case study of grade 6 multilingual learners' experiences with monolingual assessment practices in a working-class township school in Cape Town. - Cingo, Siviwe Innocent (School of Education, 2023)
This qualitative case study focusses on the experiences and challenges f multilingual learners when writing monolingual assessments. It draws on a growing body of poststructuralist theory on linguistic repertoire and translanguaging in order to understand how grade 6 multilingual learners engaged with monolingual assessments in a working-class school in the Western Cape where English is the language of learning and teaching for all learners except those for whom Afrikaans is a home language. Using ethnographic methods, I focused on 3 grade 6 classrooms and observed 46 lessons over a period of 8 weeks. In addition, I collected assessment transcripts, learners' notebooks and conducted interviews with 14 learners and their teachers. The data shows how classroom pedagogy tended to be mainly oral and dominated by teacher talk with limited space for learner engagement. Informal written assessment tasks were monolingual, but generally mediated by translanguaging and translation. Learners relied on teachers and on the linguistic resources of peers to facilitate comprehension of assessment questions and assessment content. By contrast, formal, high-stakes assessments included no mediation prior to and during assessment. Thematic analysis of learners' written answers shows how the majority of learners struggled with language comprehension at the level of vocabulary, sentence, as well as schooled academic literacy. The study concludes that both teachers and learners are placed in an untenable position by language in education policies that insist on monolingual assessment practices. Such policy results in compensatory, and contradictory classroom teaching and learning that is aimed at instrumental, assessment focused practices rather than meaningful learning. The study ends with recommendations for policy and practice.